Representation of Ukrainian Cities in Contemporary Wartime Narrative. - Kurushyna , Maryna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose: To identify peculiarities of the representation of Ukrainian cities in the war narrative, to analyze key images of these cities, to determine sustainability/transformation of the images of some Ukrainian cities since the beginning of Russia’s full-scale invasion.Methods: The paper uses the descriptive method and the content analysis to study the war narrative and further distinguish image-symbols of Ukrainian cities. The semiotic approach provides an opportunity to interpret the city as a text, a sign environment that is in constant motion and responds to internal and external challenges.Results: The representation of cities in a certain narrative and formation of their images depend on many factors, including the historical development of the city, sociocultural context, geographical characteristics, ethnic and social composition of the city, and ultimately, the leading functions of a particular city, which may be determined by the development of tourism, industry, science, etc. Russian armed aggression has led to sustainability/transformation of the images reflected in the war narrative.Conclusions: The analysis of the representation of certain Ukrainian cities in the contemporary war narrative has revealed several main trends. The cities are depicted in a personified way, possessing distinct individuality and character, and resisting the enemy. The physical loss of a city doesn’t mean a mental loss; residents literally reassemble the city from their own particularly significant places. These include both well-known locations-symbols and private spaces (associated with moments of pre-war life, a sense of the city’s spirit) that are stored in individual memory. The borderline nature of the cities is felt especially acute, the necessity to preserve the Ukrainianness and to remain a Ukrainian city that continues to function as a complete organism, becomes unbreakable and turns into a fortress, causes partial or complete irrelevance, and respectively, fewer or no mentions of other images of such cities.